Is pallial mucus involved in Ostrea edulis defenses against the parasite Bonamia ostreae? - Fernández-boo, Sergio; Gervais, Ophelie; Prado-alvarez, Maria; Chollet, Bruno; Claverol, Stéphane; Lecadet, Cyrielle; Dubreuil, Christine; Arzul, Isabelle (Journal of Invertebrate Pathology, 2020)
Bonamia ostreae is an intrahemocytic parasite that has been responsible for severe mortalities in the flat oyster Ostrea edulis since the 1970́s. The Pacific oyster Crassostrea gigas is considered to be resistant to the disease and appears to have mechanisms to avoid infection. Most studies carried out on the invertebrate immune system focus on the role of hemolymph, although mucus, which covers the body surface of molluscs, could also act as a barrier against pathogens. In this study, the in vitro effect of mucus from the oyster species Ostrea edulis and C. gigas on B. ostreae was investigated using flow cytometry. Results showed an increase in esterase activities and mortality rate of parasites exposed to mucus from both oyster species. In order to better understand the potential role of mucus in the defense of the oyster against parasites such as B. ostreae, liquid chromatography and tandem mass spectrometry were used to describe and compare mucus protein composition from both species. In all oyster species, pallial mucus contains a high level of proteins; however, O. edulis mucus produced a variety of proteins that could be involved in the immune response against the parasite, including Cu/Zn extracellular superoxide dismutase, thioxiredoxin, peroxiredon VI, heat shock protein 90 as well as several hydrolases. Conversely, a different set of antioxidant proteins, hydrolases and stress related proteins were identified in mucus from C. gigas. Our results suggest an innate immunity adaptation of oysters to develop a specific response against their respective pathogens. The mucosal protein composition also provides new insights for further investigations into the immune response in oysters.